2019
DOI: 10.1111/aogs.13631
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of hepatitis B virus DNA quantification and clinical predictors for higher viral load during pregnancy

Abstract: Introduction Authorities publish recommendations on the hepatitis B virus (HBV) viral load threshold to initiate antiviral treatment but the timing of quantification during pregnancy is not well defined. HBV DNA levels in pregnancy women at 28‐30 weeks predict the risk of immunoprophylaxis failure. This study compared and evaluated the correlation between HBV DNA levels before 22 and 28‐30 weeks’ gestation. Clinical predictive factors for HBV DNA >6, 7 and 8 log10 IU/mL were studied. Material and methods A ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
(72 reference statements)
1
1
0
Order By: Relevance
“…Positive HBeAg screening results, maternal age <35 years, and body mass index ≤21 kg/m 2 have been associated with a higher mean viral load. 15 Our study showed that 22.6% of women had viral loads of ≥200 000 IU/mL, which was comparable to previous findings. Although age was not a statistically significant factor in the present study, a previous study showed that women with high viral loads were younger than women with low viral loads.…”
Section: Discussionsupporting
confidence: 91%
“…Positive HBeAg screening results, maternal age <35 years, and body mass index ≤21 kg/m 2 have been associated with a higher mean viral load. 15 Our study showed that 22.6% of women had viral loads of ≥200 000 IU/mL, which was comparable to previous findings. Although age was not a statistically significant factor in the present study, a previous study showed that women with high viral loads were younger than women with low viral loads.…”
Section: Discussionsupporting
confidence: 91%
“…These factors have been identified as reliable markers of active HBV replication and were the only factors associated with immunoprophylaxis failure in our study. Several recent meta-analyses have reported a high incidence of MTCT associated with high HBV DNA levels above 200000 IU/mL and HBeAg-positive status despite a vaccination series associated with HBIG[ 28 , 29 ]. These findings highlight potential targets for improving prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…For women with positive HBsAg, liver function and HBV DNA should be assessed. HBV DNA quantification as early as before 22 weeks of gestation can be used reliably to predict the risk of IF and guide the use of antiviral treatment 29 . Women with high HBV DNA (>200 000 IU/mL) should be seen by a hepatologist to discuss the use of TDF after 28 weeks of gestation; whereas women with low HBV DNA should also be reminded to continue with long-term follow-up for surveillance of HBV complications (Figure ).…”
Section: Clinical Management Algorithmmentioning
confidence: 99%